Demographic Change and Border Security Governance of Nepal: An Analysis of Perceptions - Dhungel, Rudra Prasad (Journal of APF Command and Staff College, 2023)
Demographic changes in Nepal have significant implications for national security, particularly border security. The shifting populations, internal migration from rural to urban areas, and cross-border movements have given rise to various challenges like illegal border crossings, human trafficking, smuggling, and other activities that jeopardize security and stability. Despite several efforts, border security continues to be a pressing issue, and there is a lack of understanding of how locallevel elected representatives perceive the implications of demographic change on border security. This research primarily aims to analyze the perception of threat among locally elected representatives concerning the root causes of demographic change at their respective local levels. It also seeks to examine their perception of how demographic change affects border security governance and identify the security threats perceived due to such changes. Moreover, the study aims to determine the perceived role of responsible authorities or agencies in mitigating the security risks associated with demographic change. To achieve these objectives, the research follows an analytical approach, gathering perceptions from elected representatives of various local governments. It uses a combination of qualitative and quantitative methods to analyze their views on border security issues arising from changing demographics in Nepal. The focus areas are the Nepalese territories connected to neighboring countries China and India. The primary data source for the research is local-level government representatives, and the analysis involves thematic exploration of qualitative interviews and quantitative examination of population trends. However, it's important to note that the findings may have limited generalizability, as they are based solely on the perceptions of elected representatives. The study does not include perspectives from security forces or other agencies. The selected areas for the study include regions in Nepal experiencing frequent population decrease, such as Bhotekoshi rural municipality and Jugal rural municipality of Sindhupalchowk district, as well as areas with frequent population increase, including Rajdevi Municipality and Gaur Municipality of Rautahat, Nepalgunj Sub-Metropolitan City of Banke, and Bhajani Municipality and Dhangadhi Sub-Metropolitan City of Kailali District. The study sheds light on the main drivers of demographic change, such as the pursuit of better health, education, employment, and quality of life, and their long-term impact on national and border security. By engaging local-level elected representatives and employing an analytical approach, this research aims to fill the existing research gap and provide valuable information to policymakers for effectively addressing border security challenges arising from demographic change in Nepal.